2023
DOI: 10.36660/abchf.20230033
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure with Preserved Ejection Fraction in Brazil: A Systematic Review

Edimar Alcides Bocchi,
Andréa Araujo Brandão,
Evandro Tinoco Mesquita
et al.

Abstract: Heart failure with preserved ejection fraction (HFpEF) is the most common condition of heart failure (HF) in patients over 65 years of age and is associated with high morbidity and mortality. Epidemiological data on this condition are still scarce in Brazil and these data are relevant for a better understanding of the impact and unmet needs in HFpEF and for the planning of actions to improve prevention, diagnosis, and treatment of this disease.The objective of the study was to identify evidence on the epidemio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Secondly, the lack of complete outcome data raises the possibility of underreporting, affecting the accuracy and comprehensiveness of the conclusions. Despite the considerable percentage of older adults with missing data, it is unlikely to have introduced bias in the results, given the sample size, which exceeded some previous studies on the topic [23]. However, underreporting may have occurred in the final sample due to general practitioners' difficulties in diagnosing HF.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Secondly, the lack of complete outcome data raises the possibility of underreporting, affecting the accuracy and comprehensiveness of the conclusions. Despite the considerable percentage of older adults with missing data, it is unlikely to have introduced bias in the results, given the sample size, which exceeded some previous studies on the topic [23]. However, underreporting may have occurred in the final sample due to general practitioners' difficulties in diagnosing HF.…”
Section: Discussionmentioning
confidence: 84%
“…Among the 13 studies analyzed, heterogeneities were observed, including sample sizes ranging from 25 to 2056 participants, as well as different types of designs and treatment locations, both outpatient and inpatient. Surprisingly, some of the prevalences found exceeded 50%, and none of the available studies analyzed the association between HF and clustering of cardiovascular risk factors [23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations